Effects of different shrimp extracts on Vibrio parahaemolyticus growth and virulence - Nguyen Thuan Thien Truong; The Hao Nguyen; Cong Chinh Bui; Thi Thu Hoai Nguyen (Vietnam Journal of Science, Technology and Engineering, 2021)
Vibrio parahaemolyticus is the main causative agent of acute hepatopancreatic necrosis disease (AHPND) in shrimp. This study aimed to investigate how shrimp extracts affect the growth and virulence of an AHPND-causative strain known as V. parahaemolyticus XN9. To this end, the bacteria was cultured in media containing 3% extract of each of five shrimp types and their growth kinetics were compared against that from bacteria grown in brain-heart infusion (BHI) media. Eight-hour growth curves were constructed using the plate-counting method. The activity of five extracellular enzymes that contribute to bacterial virulence was examined using the agar-based method. The results showed that V. parahaemolyticus XN9’s growth was strongly enhanced in all five shrimp extract media with the highest increase (25% greater than the BHI medium) found in the giant tiger prawn extract. Additionally, all the shrimp extracts boosted the extracellular enzymatic activity of V. parahaemolyticus XN9, although to different extents. In summary, the shrimp extracts, particularly that from the prawns, not only promoted the viability and growth of V. parahaemolyticus XN9 but also its extracellular enzymatic activities.